Alternative dispute resolution: Mediation as a model [version 2; peer review: 2 approved] - Naser Sherman; Bashar Talal Momani (F1000Research)
Background The topic of Alternative Dispute Resolution (ADR) in civil and commercial contexts presents a contemporary legal challenge aimed at fostering equitable solutions. Among ADR methods, mediation stands out for its ability to reduce time, costs, and litigation duration. This study explores the conceptual framework, essential conditions, and procedural aspects of mediation. It evaluates the sufficiency, regulation, and effectiveness of mediation principles in conflict resolution and risk mitigation. Methods This study is conducted through a comprehensive review of current literature on Alternative Dispute Resolution methods, with a particular focus on mediation as an alternative to dispute settlement. The study utilizes qualitative analysis techniques to examine the effectiveness of mediation principles and their application in resolving civil and commercial disputes. Comparative analyses are also conducted to extract useful insights from various legal systems and authorities. Results The study provides an analysis that illustrates the effectiveness of mediation in resolving disputes, emphasizing its potential benefits in terms of time and cost savings, as well as its srole in facilitating amicable resolutions. The results of this study shall contribute to the current body of knowledge on mediation and provide practical recommendations for its application in diverse legal contexts. Conclusion In conclusion, the study proposes strategies to enhance mediation practices, promote a culture of its adoption, and integrate it more closely into the judicial system. Additionally, it anticipates the future effectiveness of mediation in jurisdictions lacking comprehensive legislation, drawing from successful Western experiences to guide potential developments in Arab legal frameworks.